Mogućnosti primjene univerzalnih i specijalnih kontejnera u turizmu - SKOWRON, Andrej (Promet - Traffic&Transportation, 2026)
POSSIBLE USES OF UNIVERSAL AND SPECIAL CONTAINERS IN TOURIST INDUSTRY The author discusses different possibilities of employment of individual container types in freight transport, particularly of perishable goods, to tourist destinations. Special reference is made to the possible use of containers for accommodation, i.e. accommodation of holiday-makers, vacationers and excursionists, and provides drawings of such container types as designed for housing. The author further considers it as one of the possible solutions in fire-fighting on inaccessible terrains, for regular equipment of tourist areas, and suggests the employment of containers in fire-fighting.